Efeito do tratamento com extrato padronizado de Ginkgo Biloba sobre a sinalização serotoninérgica hipotalâmica de ratas ovariectomizadas - Banin, Renata Mancini [UNIFESP] (2016)
Post-menopausal women commonly present obesity, metabolic disorders and psychiatric disturbances, which lead to a loss of life quality. Although hormone replacement therapy (HRT) ameliorates some of these symptoms, there is a higher risk for developing cardiovascular diseases and breast cancer. Thus, finding alternative therapies with minimal side effects for management of menopause-related alterations is highly desirable. We have demonstrated that Ginkgo biloba extract (GbE) reduced visceral adiposity, softened the inflammatory status in retroperitoneal adipose tissue and improved peripheral insulin sensitivity in diet-induced obese rats. The present research aimed to study, in ovariectomized rats, whether a prolonged therapy with GbE ameliorates obesity and behavioral alterations associated to ovarian hormones absence, emphasizing hypothalamic serotonin activity. 2-mo-old rats were underwent to ovariectomy (OVX) or false-ovariectomy (Sham). After surgery, body weight and food intake were measured weekly. At 4-mo-old, the rats were divided into 4 groups: Sham, Sham+GbE, OVX and OVX+GbE. The phytotherapy therapy was carried out for 14 days. The Sham+ GbE and OVX+GbE group received a daily dose of GbE (500mg/kg) diluted in 0.9% saline (vehicle) while the Sham and OVX rats received only the vehicle. During the phytotherapy treatment, body weight and food intake were measured daily. The rats were submitted to the Elevated Plus Maze and Forced Swim Tests to evaluate anxiety and depressive-like behaviors. A subset of animals received both an intracerebroventricular injection (i.c.v., lateral ventricle) of vehicle or 300g serotonin and food intake was measured 12 hours and 24 hours after each injection. In another subset of rats, a guide cannula was steriotaxically implanted in the ventromedial hypothalamus, whereby a microdialysis probe was introduced and extracellular levels of 5-HT was measured by HPLC with electrochemical detection. We evaluated the protein expression of hypothalamic serotonergic receptors 5-HT1A, 5-HT1B and 5-HT2C, the serotonin transporter (5-HTT) and the anorectic mediator POMC. Additionally, we assessed: body fat, carcass protein content, amount of liver lipids, lipid profile, alanine and aspartate aminotransferase activity (ALT/AST), serum fasting glucose, insulin, leptin, adiponectin and tumor necrosis factor-α (TNF-α) at the end of treatment. A model of Multiple Linear Regression was applied to explain anxiety and depressive-like behaviors adopting body composition measurements and serum parameters as independent variables.The OVX group showed such anxious and depressive behaviors, and it does not respond to the anorectic action of serotonin. Moreover, ovariectomy provided an excessive body mass and visceral adiposity, hyperleptinemia and dyslipidemia, characterized by an increase in total cholesterol and LDL-cholesterol. During the phytotherapy therapy, GbE promoted hypophagic effect in the OVX+GbE group, reduced symptoms of anxiety and depression and restore the effectiveness of serotonin anorectic response. On the medial hypothalamus, GbE increased extracellular serotonin levels in the OVX+GbE group. Among the metabolic effects, GbE decreased the visceral fat, increased protein carcass content, stimulated adiponectin levels, improved lipid profile and decreased the amount of liver lipids of OVX+GbE rats. Multiple linear regressions found that insulin was a predictor of anxiety in Sham rats, while treatment with GbE removed this relationship. In OVX rats, HOMA- presented an anxiolytic effect. Lower body fat and higher HDL-cholesterol levels were considered predictors for anxiolytic behavior of OVX+GbE rats. Regarding depressive-like behaviors, visceral adiposity was pointed as the most determining factor, but this relationship was not observed in the OVX+GbE rats. The phytotherapy treatment for 14 days reduced either anxious and depressed symptoms, provided a healthier body composition, improved lipid profile, enhanced extracellular levels of serotonin in the medial hypothalamus and restored the anorectic response to serotonin. Taking together all these benefic effects, it is possible that GbE might be an effective and alternative therapy for the management of menopause-related symptoms.